THE ESSENCE OF THE CONCEPT OF “PATRIOTISM” IN STUDENTS OF THE DIRECTION OF MILITARY EDUCATION UP TO THE CALL - Xolmonov Mansur Narzilloyevich (Journals Park Publishing, 2023)
Through this article, the formation of a civil duty, a sense of personal responsibility, a sense of belonging to the fate of the motherland, an active life position and a firm belief, professional skills in them by educating students of the direction of military education up to the call.
Keywords: Homeland, military-patriotic, pedagogical technology, technical and technological, personal responsibility, psychology.